Analysis of Strata Behavior Process Characteristics of Gob-Side Entry Retaining with Roof Cutting and Pressure Releasing Based on Composite Roof Structure - Manchao He; Xingen Ma; Bin Yu (Shock and Vibration)
In order to explore the characteristics of rock pressure distribution with roof cutting and pressure releasing under different composite roof structures and optimize the support design of entry retaining, the mechanical analysis and numerical simulation are used to analyze the structure characteristics of composite roof and the effect of roof cutting under composite roof in this paper. Besides, taking the 8304 working face of Tashan Coal Mine as an example, the results of theoretical research are verified by field-monitoring data of hydraulic supports, working resistance, and roadway deformation. The results show that the weak interlayer in the composite roof is easily damaged under the external force and the distribution of the layer has a key effect on the roof characteristics. When the weak interlayer is located at the middle of the roof cutting layer range, the demand of the roadway support strength is the highest; when the weak interlayer is located at the top of the roof cutting layer range, the demand of the roadway support strength is the lowest. Furthermore, with the increase of the height of the weak interlayer in the roof cutting layer range, the stress concentration peak of the coal wall side decreases first and then rises, then descends again, and the trend can be fitted by the curve of a three-degree equation.